AXIOLOGY OF THE DOCUMENT IN THE ACTIVITIES OF THE NATIONAL POLICE OF UKRAINE - Stanislav Pevko (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. In this article, a comprehensive analysis of determining the value of a document in the activity of the National Police in Ukraine is carried out in order to establish the significance of documents in police activity. Police officers work and process a large number of documents that directly affect the legality of the exercise of authority and the level of effectiveness of this body. Therefore, the question of the significance of documents in police activity is quite important.